Quality of life after transcatheter tricuspid valve repair: results from the Tri.FR trial - Sabina Istratoaie; Pascal deGroote; Nicole Karam; Jean‐Noel Trochu; Guillaume Leurent; Augustin Coisne; Pierre‐Yves Le Roux; Anne Ganivet; Anne Bernard; Antoinette Neylon; Romain Pierrard; Florent Le Ven; et al. (ESC Heart Failure)
Abstract Aims In the Tri.FR trial, tricuspid transcatheter edge‐to‐edge repair (T‐TEER) reduced severity of tricuspid regurgitation (TR) and improved the composite clinical score, driven by patient‐reported outcomes. The purpose of this study was to describe the longitudinal impact of T‐TEER on different dimensions and items of quality of life compared with guideline‐directed medical treatment (OMT) alone. Methods and results Patients were randomized to T‐TEER +OMT (n = 152) or OMT alone (n = 148). Health status was assessed at baseline, 6 weeks, 6 months, and 1 year using the Kansas City Cardiomyopathy Questionnaire (KCCQ) and the Minnesota Living with Heart Failure (MLHF) Questionnaire. Mixed effects linear regression analysed changes over time. Patients receiving T‐TEER + OMT experienced a significant increase in KCCQ overall summary score (KCCQ‐OS) at all time points: +17.0 points (95% confidence interval [CI] 13.1–21.5) at 6 weeks, +15.9 points (95% CI 11.2–20.6) at 6 months, and +18.7 points (95% CI 13.8–23.6) at 1 year. The mean between‐group difference in KCCQ‐OS was +10.3 points (95% CI 5.6–15.0) in favour of T‐TEER + OMT, evident at 6 weeks and sustained for 1 year. Similarly, MLHF total scores improved significantly in the T‐TEER group (mean between‐group difference −8.61 points, 95% CI –12.6 to −4.6), including physical (−3.9, 95% CI –5.9 to −1.9) and emotional (−2.2, 95% CI –3.4 to −1.0) subscales. Conclusions Compared with OMT alone, T‐TEER resulted in substantial, multidimensional, and sustained improvements in patient‐reported quality of life. These findings reinforce the value of T‐TEER in managing severe symptomatic TR.